Optimization Extraction Conditions for Phenolic Compounds, Antioxidant and Inhibitory Activities of Angiotensin I‐Converting Enzyme (ACE), α‐Glucosidase and α‐Amylase from Mentha Spicata L. Issue 3 (20th November 2015) - Alu'datt, Muhammad H.; Rababah, Taha; Alhamad, Mohammad N.; Ereifej, Khalil; Al‐Mahasneh, Majdi; Brewer, Susan; Rawshdeh, Mervat
Abstract: Ideal extraction conditions were estimated based on the maximum phenolic content, antioxidant activity and inhibitory activity of angiotensin‐converting enzyme (ACE), α‐glucosidase and α‐amylase enzymes from M entha spicata L. The optimum extraction conditions for phenolic compounds with maximum ACE inhibitory activity occurred in a mixture of acetone and water (1:1) at 40C for 6 h. The optimal extraction conditions for phenolic compounds with maximum α‐amylase and α‐glucosidase inhibitory activity were obtained in a mixture of methanol, acetone and water extraction (1:1:1) and in a mixture of methanol and distilled water (1:1) at 50C for 8 h. The major free phenolic compound extracted with the various extraction solvents, times and temperatures was rutin. The predominant bound phenolic compounds were caffeic acid and chlorogenic acid, which did not exist as free phenolic compounds. Practical Applications: This study suggested the optimum extraction conditions of phenolic compounds with maximum capacity of antioxidant, antihypertensive and antidiabetic properties recommended to be used in food industry as pharmaceutical and nutraceutical herbal extract.